National census of UK endoscopy services 2021. Issue 6 (9th May 2022) - Ravindran, Srivathsan; Thomas-Gibson, Siwan; Bano, Madeline; Robinson, Emma; Jenkins, Anna; Marshall, Sarah; Ashrafian, Hutan; Darzi, Ara; Coleman, Mark; Healey, Chris
Abstract : Introduction: The Joint Advisory Group on Gastrointestinal (GI) Endoscopy (JAG) biennial census provides a unique view of UK endoscopy. The 2021 census was conducted to understand the impact of ongoing pressures, highlighted in the previous census, as well as COVID-19. Methods: The census was sent to all JAG-registered services in April 2021. Data were analysed across the domains of activity, waiting time targets, workforce, COVID-19, safety, GI bleeding, anaesthetic support, equipment and decontamination. Statistical methods were used to determine associations between domain-specific outcome variables and core demographic data. Results: 321 services completed the census (79.2% response rate). In the first 3 months of 2021, 57.9% of NHS services met urgent cancer waits, 17.9% met routine waits and 13.4% met surveillance waits. Workforce redeployment was the predominant reason cited for not meeting targets. There were significant regional differences in the proportion of patients waiting 6 or more weeks (p=0.001). During the pandemic, 64.8% of NHS services had staff redeployed and there was a mean sickness rate of 8.5%. Services were, on average, at 79.3% activity compared with 2 years ago. JAG-accredited services are more likely to meet urgent cancer waits, with a lower proportion of patient waiting 6 weeks or more (p=0.03). Over 10% of services stated that equipment shortage interfered with service delivery. Conclusions: Services are adapting to continued pressure and there are signs of a focused response to demand at a time of ongoing uncertainty. This census' findings will inform ongoing guidance from JAG and relevant stakeholders.